Ultralow diffusion barrier induced by intercalation in layered N-based cathode materials for sodium-ion batteries. Issue 12 (13th March 2023) - Jiang, Yundan; Xu, Wangping; Zhao, Wei; Cao, Juexian
Abstract : Layered 2H-phase CrN2 with Cs intercalation possesses many advantages including an ultra-low diffusion barrier (0.04 eV), high voltage platform (3.9 V), and high energy density (903 W h kg −1 ), and is a promising candidate for SIB cathode materials. Abstract : Sodium-ion batteries (SIBs) have attracted huge attention due to not only the similar electrochemical properties to Lithium-ion batteries (LIBs) but also the abundant natural reserves of sodium. However, the high diffusion barrier has hindered its application. In this work, we have theoretically studied the relationship between the strain and the diffusion barrier/path of sodium ions in layered CrN2 by first-principles calculation. Our results show that the strain can not only effectively decrease the diffusion barrier but also change the sodium diffusion path, which can be realized by alkali metal intercalation. Moreover, the diffusion barrier is as low as 0.04 eV with the Cs atoms embedding in layered CrN2 (Cs1/16 CrN2 ), suggesting an excellent candidate cathode for SIBs. In addition, the decrease of the barrier mainly originated from the fact that interlayer electronic coupling weakened with the increase of interlayer spacing. Our findings provide an effective way to enhance sodium diffusion performance, which is beneficial for the design of SIB electrode materials.